A method for the purification of bacterial flagellin that allows simple upscaling - Hiriart, Yanina (2012)
There is a growing interest in enterobacterial flagellins that may result in a demand to produce flagellin on an industrial scale for possible applications as an adjuvant, immunomodulatory agent or vaccine antigen. Traditionally, small-scale production of flagellin has occurred in the laboratory by flagellar shearing of bacterial surfaces and subsequent ultracentrifugation. The main drawback of this method is the need to use low-agitation cultures to avoid the loss of flagella due to shearing during culture. In the present work, we describe a scalable protocol for the production of flagellin with higher yields than traditional laboratory-scale protocols. The use of cross-flow filtration to concentrate bacterial cultures combines extensive shearing of flagella with a reduction in volume, greatly simplifying downstream processing. This technique also allows the use of highly-agitated culture conditions because any sheared flagella are retained in the bacterial concentrate. Flagella obtained with this procedure showed in vivo and in vitro innate activating capacities similar to those of flagella produced at laboratory scale. This procedure is flexible, allowing an increase in production scale, an enhancement of flagellin yield and no requirement for expensive equipment.